Evaluating the standardized ileal digestible Histidine:Lysine requirement for 15 to 25 lb pigs - Karns, Rebecca; Cemin, Henrique; Tokach, Michael D.; Woodworth, Jason C.; Dritz, Steven S.; Goodband, Robert D.; Touchette, K.; Lerner, Anne B. (My University, 2018)
Histidine may be the sixth limiting amino acid in practical nursery diets formulated with high inclusion of crystalline amino acids. The first five limiting amino acids are available in feed-grade forms, meaning diets are formulated to the histidine requirement. Thus, the objective of this study was to determine the SID His:Lys requirement of 15 to 25 lb pigs. In total, 350 pigs were placed in pens of 5 pigs/pen. The pigs were fed a common pelleted diet for 10 d post-weaning. At d 10, (considered day 0 of the study), pens were assigned to treatment in a completely randomized block design with body weight as the blocking factor. The pigs were fed the experimental diet d 0 to 14 and a common diet was fed d 14 to 28. There were 7 pens/treatment. Treatments consisted of increased SID His:Lys ratio of 24, 28, 30, 32, 34, 36, or 42%. Diets were corn, spray-dried whey, and whey protein concentrate-based and treatments were formed by adding L-His at the expense of corn. Pigs were weighed and feed disappearance was measured on d 0, 7, 14, 21, and 28 to compute ADG, ADFI, and F:G. Data were analyzed with the GLIMMIX procedure of SAS and dose-response models were fitted to determine the SID His:Lys requirement. From d 0 to 14, ADG and F/G improved then plateaued (quadratic, P<0.001) and ADFI linearly increased (P<0.001) with increasing SID His:Lys. The SID His:Lys requirements were estimated at 31% for ADG and 28.6% for F/G. From d 14 to 28, the post-test period, ADFI increased (linear, P=0.003) and F/G worsened (quadratic, P=0.002) in pigs previously fed diets with increasing SID His:Lys. Results from this study support the results of a prior experiment performed at Kansas State University, where SID His:Lys requirement ranged from 29-30%. Conclusively, the SID His:Lys requirement of 15 to 25 lb pigs ranged from 28.6 to 31%. The current NRC (2012) recommendation is 34% SID His:Lys, which is higher than the requirements observed in this study. Therefore, practical nursery diets can be formulated with high inclusion of crystalline amino acids without compromising required SID His:Lys.
Keywords: Spring 2018